PROFESSIONAL ETHICS ADVOCATES AS CONTROLLING EFFORTS IN PERFORMING LAW ENFORCEMENT FUNCTIONSAS AN ADVOCATE - Agus Pramono (UNTAG Law Review, 2017)
Advocate as one element of the judicial system is one of the pillars in upholding the supremacy of law and human rights. Advocates are noble professions closely related to humanity. The Advocate Profession in providing legal services and in charge of solving legal problems of his clients both in litigation and non- litigation, so he is required to always participate in the enforcement of Human Rights, and in running his profession he is free to defend anyone, not bound by orders Regardless of who the opponents of his client, whether he is from strong groups, rulers, officials and even poor people though. The Advocate function within the scope of work of the modern Advocate shows two aspects, namely 1). Represent the client before the Court; And 2). Representing clients outside the Court. Advocates as noble professions must uphold the laws and regulations of the code of ethics, so that if a violation is detrimental to the profession or the client should get the action in the form of sanctions imposed also did not eliminate the right to continue running the profession. This is where the dignity of an advocate remains respected while sanctions are a form of repression for the offenses committed.